Hidrólise com água subcrítica do bagaço de sorgo sacarino (Sorghum Bicolor L. Moench) pré-tratado com o líquido iônico [Bmim]Cl visando a obtenção de bioprodutos e açúcares - Bragato, Carolina Almeida (2021)
In this research, the saccharine sorghum bagasse was submitted to a pre-treatment with an ionic liquid, 1-butyl-3-methylimidazolium [Bmim] Cl in order to evaluate the effect on the undissolved solid after the pre-treatment in relation to the cellulose contents, hemicelluloses and lignin. Two pretreatment facilities were evaluated, 100 and 120 °C. The increase in hemicellulose groups required for pretreatments at temperatures of 100 and 120 °C with a biomass/eutectic solvent ratio of 1:10 in 2 was evaluated, 4 and 6h using Fourier transform infrared spectrophotometry The pretreatment of saccharine bagasse was also evaluated in relation to a lignicellulosic composition by thermogravimetric analysis and the derivative of thermograms (DTG) generated. From the integration of the DTG peaks (in well defined intervals defined by the literature) the contents of cellulose, hemicelluloses and lignin were determined, both in pre-treated and in natura. The pre-treatment condition that generated a biomass rich in hemicelluloses and greater delignification was provided as best, and the biomass from the pre-treatment was used in the subsequent hydrolysis step. Subcritical hydrolysis was performed in a reactor in semi-continuous operation mode. The process variables were studied: temperature (220 and 260 ° C) and solvent/feed mass ratio (80 and 100). The pressure was set at 15 MPa and the total reaction time was 10 min. The highest yield of fermentable sugars (19.18 ± 0.50 g / 100 g biomass) was obtained for saccharine bagasse pretreated with [Bmim] Cl with water under the reaction condition in the 220 ° hydrolysis step C in the solid/solvent ratio of 100. For fresh sorghum bagasse the yield, under the same condition, was 09.36 ± 0.35 g / 100 g biomass. Sugar sorghum bagasse pretreated with ionic liquid presented a yield 2.05 times greater than fresh sorghum bagasse.